2014
DOI: 10.1038/mp.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

HMGCR is a genetic modifier for risk, age of onset and MCI conversion to Alzheimer’s disease in a three cohorts study

Abstract: Several retrospective epidemiological studies report that utilization of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) inhibitors called statins at mid-life can reduce the risk of developing sporadic Alzheimer’s disease (AD) by as much as 70%. Conversely, administration of these inhibitors in clinically diagnosed subjects with AD confers little or no benefits over time. Here, we investigated the association between AD and HMGCR rs3846662, a polymorphism known to be involved in regulation of HMGCR exon 13 sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 59 publications
(84 reference statements)
2
54
1
Order By: Relevance
“…Both higher FCRP and higher Aβ burden were associated with less cortical thinning in subjects that were taking cholesterol-lowering drugs when compared with subjects who were not taking cholesterol drugs. This finding, which needs replication, is in line with other studies suggesting that statins confer some level of neuro-protection against late-life development of AD 39, 40 , see also 41 . Given that statin treatment has shown no reliable effect on clinical symptoms in subjects with dementia, it is more than plausible that statins only have an impact when started in midlife.…”
Section: Aβ and Vascular Risk Factors: Independent Or Dependant Pathwsupporting
confidence: 90%
“…Both higher FCRP and higher Aβ burden were associated with less cortical thinning in subjects that were taking cholesterol-lowering drugs when compared with subjects who were not taking cholesterol drugs. This finding, which needs replication, is in line with other studies suggesting that statins confer some level of neuro-protection against late-life development of AD 39, 40 , see also 41 . Given that statin treatment has shown no reliable effect on clinical symptoms in subjects with dementia, it is more than plausible that statins only have an impact when started in midlife.…”
Section: Aβ and Vascular Risk Factors: Independent Or Dependant Pathwsupporting
confidence: 90%
“…Of note, Keller et al [51] recently highlighted an association between a polymorphism within the HMGCR promoter, rs3761740, and transcriptional activity by SREBP. Yet, we previously confirmed that this polymorphism was in linkage disequilibrium with rs3846662 (linkage disequilibrium 0.97) [32]. These two SNPs might thus act in concert to modulate HMGCR mRNA levels, at least in FH, in which the cholesterol metabolism is substantially deregulated.…”
Section: Discussionmentioning
confidence: 82%
“…), and epistasis between those genes may be responsible for the association between AA and suboptimal statin response in FH women. Evidence for epistasis for rs3846662 has previously been demonstrated: rs3846662 interacts with one locus in hepatic lipase (LIPC) to modulate HDL-C levels [49], and rs3846662 modulates Alzheimer's disease risk in women only [32], a finding suggesting an epistatic interaction between HMGCR and genotype defined by the X and Y chromosomes [50]. Of note, Keller et al [51] recently highlighted an association between a polymorphism within the HMGCR promoter, rs3761740, and transcriptional activity by SREBP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations